From dealing to influencing: online marketing of cannabis on Instagram - Anderdal Bakken, Silje (Crime, media, culture, 2023)
In this paper we argue that legal and technological shifts in cannabis marketing has a gendered impact, which research so far has ignored. Despite high variations in national criminal laws, US-based social media platforms like Instagram, Facebook, and Twitter play a huge role in enforcing certain social and political standpoints on a global scale. One example being the recent legalization and commercialization of cannabis in various states in the US. Young men with dark, anonymous profiles illegally dealing cannabis on social media are no longer the only visible traders, as today?s marketing of trademarked legal cannabis products also features women influencers, who post images exhibiting light colors, desirable environments, and beautiful landscapes. To understand this diversity, we compared 60 Instagram profiles of illegal Swedish cannabis sellers to 70 US-based cannabis influencers? Instagram profiles. By applying theories and research from media scholars on influencing, we highlight various changes in the way cannabis is being presented and professionalized by a new group of actors. Our findings show that cannabis influencers on Instagram are changing the stereotypical characteristics of illegal cannabis culture as being almost entirely dominated by men, to one where cannabis is represented as a desirable accessory in certain feminine lifestyles. Influencers? role in transforming cannabis culture to become more mainstream and acceptable for women could potentially effect cannabis cultures globally, as well as ongoing legalization debates.